PEMBUATAN GAME ILMU SHOROF (TASHRIEF) SEBAGAI MEDIA PEMBELAJARAN BAHASA ARAB - Undang Syaripudin; Yana Aditya Gerhana; Hafizh Hasanudin (JURNAL ISTEK, 2012)
It requires real good knowledge to create fine and qualified interactive multimedia products. Interactive multimedia must be completed with contents which can be controlled by the users. Instructional Games model is one of the interactive multimedia subjects which based on computer.This game model could be used to overcome difficulties in learning Arabic. The difficulties in learning Arabic, especially in Shorof, are about changing, transforming, and developing a word into new forms or to track back to its derivations. The goal of this game is to help students to study shorof. So the students could memorize wazan tashrief of every chapter of tsulatsi and ruba’i.Development methode which was used for this game is Luther Sutopo multimedia development version. It has six steps of development methode. Those are concept, design, material gathering, processing, examination, and distribution. Games which were made based on separation of wazan tashrief are tsulatsi mujarrad, tsulatsi mazid I, tsulatsi mazid II, tsulatsi mazid III, ruba’i mujarrad I, ruba’i mujarrad II. Those games have to be tested by the games makers at first place, then given to Arabic teachers to figure out their responses.